Tantangan Sosial Masyarakat Pedesaan dalam Menghadapi Perkembangan Desa Wisata di Desa Giritengah, Borobudur, Magelang, Jawa Tengah - Ngadisih; Nabila, Kharisma; Achmad Solikan (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2023)
Tourism villages in Indonesia are villages that have a diversity of typical village potentials in the form of culture, nature, and agricultural products to be exhibited to tourists. However, in its development, tourism villages can provide challenges for village communities. This article aims to map the problems faced by Giritengah cultural tourism village in socio-cultural aspects and preservation efforts on the problems that occur. This research uses data collection methods in the form of literature studies and paritisipatory observations. The literature study conducted in this study was conducted by examining the social challenges of rural communities through selected literature sources, namely from scientific articles, books, theses, theses, and dissertations. Participatory observation in this study was carried out through direct observation to find out how life is in the Giritengah village community. The results of this study show that the challenges faced by the people of Giritengah village are in the form of shifts in the field of work. In 2016, work was dominated by farmers, while in 2021, the people of Giritengah village have known various kinds of jobs and the highest is to become private employees. Based on this, cultural preservation efforts are needed. Cultural preservation can be done through cooperation between village administrators and parties outside the village to be able to unite the vision and mission in line with the preservation of village culture and tourism villages, then the village can coordinate in various sectors of society, both rural communities and communities outside the village so that there are no conflicts of interest between groups. This is intended to be able to maintain the preservation, authenticity, and harmony of natural and cultural products from the Giritengah village community.